Attitudes, patterns and awareness on the use of self-medication and non-doctor prescription methods among undergraduate medical, nursing and physiotherapy students of a tertiary care setting in south Gujarat - Singh, Sahil; Balusamy, Divakar; Sinha, Anita; Verma, Mamtarani; Jain, Dhairya (Indian Journal of Community Health, 2023)
Background: According to WHO Self-medication can be defined as the use of drugs to treat self-diagnosed disorders, or the intermittent or continued use of a prescribed drug for chronic or recurrent disease or symptoms. Aim & Objective: To assess and improve the level of awareness regarding self-medication non-prescription medicines and over the counter drugs, to assess the prevalence and determinants of self-medication practices among undergraduate students. Settings and Design: A cross-sectional study design was used to carry out a study at tertiary care centre. Methods and Material: Sociodemographic characteristics, self-medication knowledge and general questions on self-medication were asked from study participants. Statistical analysis used: SPSS software version 26. Self-medication knowledge was scored and categorized as excellent/good and poor knowledge. Comparison of knowledge scores among medical, nursing and physiotherapy students was done using ANOVA test. Results: The prevalence of OTC drug usage was found out to be 304(79.4%). Highest prevalence was noted amongst medical students i.e., 186(83.4%) followed by nursing and physiotherapy students which were similar at 55(73.3%) and 63(74.4%) respectively. Mean knowledge scores of MBBS, nursing and physiotherapy students showed significant results with F-statistic value of 21.63 (p=0.00). Conclusions: Self-medication happens to be a common practice among medical and paramedical students.